Targeting the PI3K/AKT signaling pathway: an important molecular mechanism of herbal medicine in the treatment of MASLD/MASH - Jiang, Shan; Zhai, Li; Shao, Yingchun; Sun, Fusheng; Liu, Xuedong (Frontiers in Nutrition, 2026)
Metabolic dysfunction-associated steatotic liver disease (MASLD) was once known as non-alcoholic fatty liver disease (NAFLD). MASLD and its progressive form metabolic dysfunction-associated steatohepatitis (MASH) have become significant challenges in global public health with their incidence rates showing a persistent upward trend. MASLD is the result of multiple factors acting simultaneously. Multiple biochemical cycles and molecular pathways are implicated in the pathogenesis of MASLD/MASH, such as the phosphoinositide 3-kinase (PI3K)/ protein kinase B (AKT) signaling pathway. Natural products are considered a treasure for new drug discovery and are of great value to medicine. Natural products mediate their therapeutic effects on MASLD/MASH, at least in part, by modulating the PI3K/AKT signaling pathway. However, at present, there are relatively few systematic reviews and summaries in this field both domestically and internationally. This review systematically examines the molecular mechanisms through which the PI3K/AKT signaling pathway contributes to the pathogenesis of MASLD/MASH. Additionally, it places particular emphasis on the potential of natural compounds targeting this pathway as a preventive strategy against MASLD/MASH. It is evident that the PI3K/AKT signaling pathway plays an important role in the progression of MASLD/MASH. Natural products belonging to various classes, such as phenylpropanoids, flavonoids, terpenoids, and alkaloids, can alleviate MASLD/MASH and the mechanisms involve regulation of the PI3K/AKT signaling pathway. Herbal medicines hold significant research potential in modulating the PI3K/AKT signaling pathway to improve MASLD/MASH. An in-depth understanding of these pharmacological mechanisms will help design precise intervention strategies to effectively interrupt or reverse disease progression.